2008
DOI: 10.1097/cad.0b013e3283114fb2
|View full text |Cite
|
Sign up to set email alerts
|

Activity of lipoplatin in tumor and in normal cells in vitro

Abstract: Lipoplatin is a novel liposomal cisplatin formulation with reduced adverse side effects compared with its parental compound, cisplatin. The aims of this preclinical study were to compare lipoplatin and cisplatin cytotoxicity in vitro in established cell lines derived from non-small cell lung cancer, renal cell carcinoma, and in normal hematopoietic cell precursors, and to identify biological markers associated with sensitivity and resistance. Our results showed a superior cytotoxicity in all tumor cell models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…Same trend was observed with Lipoxal™, which was better tolerated with fewer side effects than in patients receiving oxaliplatin [6]. Reduction of the systemic toxicity with Lipoplatin™ and Lipoxal™ did not seem to decrease their therapeutic potential, as suggested by preclinical and few clinical reports [9,10].…”
Section: Introductionmentioning
confidence: 74%
“…Same trend was observed with Lipoxal™, which was better tolerated with fewer side effects than in patients receiving oxaliplatin [6]. Reduction of the systemic toxicity with Lipoplatin™ and Lipoxal™ did not seem to decrease their therapeutic potential, as suggested by preclinical and few clinical reports [9,10].…”
Section: Introductionmentioning
confidence: 74%
“…Lipoplatin was ‘tested’ in combination with gemcitabine in a phase I–II trial of advanced pancreatic cancer where doses higher than 100–150 mg/m 2 of lipoplatin were well tolerated [19]. Other trials have shown low or negligible nephrotoxicity and tumor effectiveness in vivo and in vitro [19, 20]. The dose of lipoplatin administered alone is tolerated even at the level of 350 mg/m 2 (G.P.…”
Section: Introductionmentioning
confidence: 99%
“…Comparative studies in rodents and dogs showed a clear superiority of Lipoplatin over cisplatin in terms of kidney tubular damage (14,15). Moreover, Arienti et al showed a higher antitumor activity of Lipoplatin in established cell lines from various tumors (16). The observed favorable toxicity and anti-tumor efficacy of Lipoplatin compared with cisplatin suggest a higher therapeutic index for Lipoplatin.…”
Section: Discussionmentioning
confidence: 96%